Salmon and acorns feed our people : colonialism, nature, and social action - Norgaard, Kari Marie (Nature, society, and culture., 2019)
"Once the third largest salmon-producing stream in the Western United States, the Klamath River has, as of 2014, fallen to only 4% of its previous productivity. This gives the once wealthy Karuk Tribe the dubious honor of having one of the most dramatic and recent diet shifts in North America. Unable to fulfill their traditional fishermen roles, Karuk people are now among the most impoverished in the state. In Salmon and Acorns Feed Our People, noted environmental sociologist Kari Norgaard investigates how their inability to fish affected the sense of identity and self-esteem of Karuk men. How does environmental degradation inscribe racialized power relations or do the work of colonial violence? Salmon and Acorns Feed Our People tells a story set in the cultural and political experiences of the Karuk Tribe, while expanding theoretical conversations on health, identity, food, race, and gender that preoccupy many disciplines today."--